Compressibility Effects on Turbulent Heat Transfer of Natural Convection in a Square Cavity - Mahmudah, Rida Siti Nur'aini; Widiatmono, Restu; Darmawan, Denny (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
Heat transfer in turbulent flows is one of the essential topics in power plants and thermal-based engineering. This study aims to analyze the effects of density changes due to heat transfer in a turbulent environment—which is usually neglected because it can cause instability in a simulation. We simulate an available experimental case of turbulent heat transfer of air with OpenFOAM: one with an incompressible approach (no density change) and another with a compressible treatment. The simulation geometry is a 0.75 × 0.75 m2 square cavity, where its left and right walls are kept at a temperature difference of 40 K. We compare and analyze the temperature, velocity, and turbulence kinetic energy profiles of both simulation results against the experimental data. We found that from all qualitative and quantitative comparisons, the change in density plays a vital role in turbulent heat transfer. The compressible treatment gives better results than the incompressible: the neglection of density change causes a significant difference with the experimental data. Thus, we strongly recommended incorporating compressibility in simulating heat transfer in turbulent flows.